Attitudes and Preferences of Local Visitors Toward Ecotourism Sites in Bahrain - Alsamawi, H (KnE Social Sciences, 2018)
The tourism industry has become one of the most considerable economic sectors in the world. Gulf countries especially Bahrain included tourism as one of the most important exports that will help to diversify the country GNP dependence on oil exporting only. The main concern of ecotourism is to encourage the local inhabitants to involve in tourism activities, and stresses on conservation of nature by educating the visitors how to protect and respect the culture visited. This article is a behavioraloriented study that investigates and explains the preferences of tourists toward selected tourism sites in Bahrain. It is composed in twofold: first, it presents the research approach and the selection of the analyzed sites; second, it presents the findings concerning tourists’ demographic and socioeconomic characteristics, tourism participation rates, and preferences toward tourism quality and levels of satisfaction. Data were collected by means of questionnaire interviews. 706 questionnaires were analyzed. Findings demonstrated the importance of the tourists’ concerns in tourism planning process. The study also shows that variations in preferences and attitudes rates resulted from the differences in socioeconomic characteristics of tourists. Keywords: Bahrain, Behavioral Approach, Ecotourism, Tourism Planning, Attitudes, Preferences